Molecular analysis of katG gene mutations in strains of Mycobacterium tuberculosis complex from Africa - Haas, Walter; Schilke, Kathrin; Brand, J.; Amthor, Beate; Weyer, K.; Fourie, P. B.; Bretzel, Gisela; Sticht-Groh, Veronica; Bremer, Hans J. (Antimicrobial agents and chemotherapy, 1997)
A sample of 124 isoniazid (INH)-resistant and 88 susceptible strains of Mycobacterium tuberculosis complex from south, central, and west Africa was analyzed by direct sequence analysis and PCR-restriction fragment length polymorphism analysis of their catalase-peroxidase (katG) genes. Point mutations at codon 315 were found in the genomes of 64% of INH-resistant strains, but no complete deletions were identified. Mutations at codon 463 were independent of INH resistance and were linked to the geographic origins of the strains.